2022
DOI: 10.1136/postgradmedj-2022-141541
|View full text |Cite
|
Sign up to set email alerts
|

Improving resident well-being: a narrative review of wellness curricula

Abstract: BackgroundTo improve wellness among residents, many graduate medical education programs have implemented formal wellness curricula. Curricular development has recently shifted focus from drivers of burnout to promotion of wellness. The specific components of successful wellness curricula, however, are not yet well defined.ObjectiveTo review the published literature assessing core components of wellness curricula in graduate medical education programs.MethodsSearches were conducted through June 2020 in PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Interventional studies also revealed WHL, formal mentorship programs and resident wellness programs to be protective against burnout among surgical residents and WHL and resiliency programs to be protective for non-surgical residents. These factors are consistently reported in literature in association with resident well-being and are focused areas of residency program improvements (Raj, 2016;Ahart et al, 2023;Safety et al, 2009). These also highlight ubiquitous fundamental principles of high-quality residency education shared across all medical specialties.…”
Section: Discussionmentioning
confidence: 80%
“…Interventional studies also revealed WHL, formal mentorship programs and resident wellness programs to be protective against burnout among surgical residents and WHL and resiliency programs to be protective for non-surgical residents. These factors are consistently reported in literature in association with resident well-being and are focused areas of residency program improvements (Raj, 2016;Ahart et al, 2023;Safety et al, 2009). These also highlight ubiquitous fundamental principles of high-quality residency education shared across all medical specialties.…”
Section: Discussionmentioning
confidence: 80%